Society explained an introduction - Rousseau, Nathan 1957- (Lanham, Maryland Rowman & Littlefield, 2014)
"Introduces key concepts in sociology through engaging narrative examples. After an overview of the history of sociology, the book walks readers through subjects that include individualism; culture; socialization and imagination; values, money, and politics; marriage and family; religious diversity; and education and social change."--Publishers website.
Observing social life -- Individuals and the structure of society -- Culture -- Socialization and imagination -- Values, money, and politics -- Sex, marriage, family, and community -- Religion -- Education, science, and the informed citizen.
Includes bibliographical references (pages 259-273) and index.
Keywords: Sociology